ENHANCING COMPETENCIES OF QUANTITY SURVEYORS IN COST MANAGEMENT OF MECHANICAL AND ELECTRICAL SERVICES - Adetunji Arowoiya, Victor; Akinradewo, Olusola Festus; Oke, Ayodeji Emmanuel (Journal of Surveying, Construction and Property, 2022)
Quantity surveyors (QS) play an important role in any construction projects such as mechanical and electrical (M&E) projects but there has been less participation of the profession. The study is aimed at improving QS competencies to provide better cost management for M&E services. A mixed methodology was used for this study, the questionnaire was structured on a five-point Likert scale to elicit the opinion of respondents. Semi-structured interviews were also conducted with some experts in M&E services who have met some criteria for selection. Descriptive and Inferential statistical method was used in the analysis of data collected. The most important strategies for the cost management of M&E projects were site exposure of QS to M&E works, advanced educational training of M&E services, as well as improvement of QS curriculum to multidimensional needs and expected standard for M&E, works. Kruskal Wallis was adopted to examine the difference in the opinions of professionals. The results showed that all the professionals have different opinions for all the variables except for the QS curriculum should be updated to multidimensional needs and expected standard M&E works. The study concluded that for the competencies of quantity surveyors to be enhanced, there is a need for exposure to M&E works and training should meet up to the expected standard of client needs. The study recommends that academic institutions and professional bodies should update the curriculum to the multi-dimensional needs of clients so that graduate QSs will be able to face the challenges and threats in the industry.